RELIGIUS TETAPI RAPUH: PARADOKS NILAI PENDIDIKAN AGAMA HINDU PADA KEHIDUPAN MAHASISWA HINDU MASA KINI - I Made Arya Artha Swandra (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to analyze the paradox of Hindu Religious Education values in the lives of contemporary Hindu university students, particularly the gap between visible religious expressions and the internalization of religious values in everyday life. The research employed a qualitative approach within an interpretive-constructivist paradigm using a case study design. Data were collected through in-depth interviews, observations, and document analysis involving Hindu students and relevant supporting informants. Data were analyzed thematically through data reduction, coding, categorization, and inductive interpretation. The findings reveal that Hindu students generally maintain a strong religious identity, reflected in their participation in religious rituals, spiritual activities, and faith-based student organizations. However, strong religious expression does not necessarily correspond to a deep internalization of Hindu religious values. Students continue to face challenges in practicing the values of dharma, morality, and Tri Kaya Parisudha amidst the influences of digital media, changing lifestyles, academic pressures, and contemporary social dynamics. The study indicates that students’ religiosity tends to develop at a symbolic level, while religious value resilience remains insufficiently established. Therefore, Hindu Religious Education should be strengthened through more reflective, contextual, and transformative learning approaches to foster a stronger integration between religious knowledge, spiritual awareness, and practical implementation of religious values in students’ daily lives.